2006
DOI: 10.1116/1.2388967
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic chucking for extreme ultraviolet lithography: Simulations and experiments

Abstract: The purpose of this research is to assess the effectiveness of electrostatic chucks in reducing low-spatial frequency mask ͑or reticle͒ flatness variations and to validate finite element ͑FE͒ models of the chuck-mask interaction. The flatness of a sample extreme ultraviolet lithography reticle and an electrostatic pin chuck were measured using a Zygo interferometer. The measured flatness data were entered into the FE models, and electrostatic chucking was simulated by applying an area-weighted average pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…If we plot c T x , c T z and c p (see Fig. 2), two observations can be made: first, high spatial frequencies will be damped by the material and are not expected to be transmitted to the front-side (see (6) and (7)); second, for givenσ bs zz = p, the corresponding back-side amplitudeū bs z decreases as k increases (see (5)). …”
Section: Harmonic Warpingmentioning
confidence: 95%
See 1 more Smart Citation
“…If we plot c T x , c T z and c p (see Fig. 2), two observations can be made: first, high spatial frequencies will be damped by the material and are not expected to be transmitted to the front-side (see (6) and (7)); second, for givenσ bs zz = p, the corresponding back-side amplitudeū bs z decreases as k increases (see (5)). …”
Section: Harmonic Warpingmentioning
confidence: 95%
“…One method to predict for the mask deformation is based on the finite element analysis. [4][5][6] While providing the presumably most accurate results, these simulations are computationally expensive -especially when a dense mesh is needed to resolve small features of the mask and chuck non-flatness measurement. In this article we propose a new analytical method to compute the mask OPD and IPD based on the solution of the mechanical equilibrium equations in the context of linear elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the necessity of performing all experiments in a vacuum environment. 3 A Zygo GPI system was positioned vertically over the chamber to enable measurements of the mask nonflatness through the top viewport. Figure 6(a) is a photograph of this viewport, which uses a fused silica flat with a diameter of 8.0 in.…”
Section: Custom-built Experimental Setupmentioning
confidence: 99%
“…8͒. 2 To simulate chucking of the individual masks, interferometric data from the two masks and the chuck were used as input into the models. Contact friction between the backside of the mask and the surface of the chuck has been previously measured for typical EUVL materials and was assumed to be 0.2 in all of the models.…”
Section: Comparison Of Experimental Data With Predictionsmentioning
confidence: 99%